Edukasi Kreatif Pengolahan Limbah Botol menjadi Pot Bunga sebagai Upaya Peningkatan Kesadaran Lingkungan di SDN Jari 2 - Indriani, Yulia; Tunggal Dewi, Tahta Tribuana; Bilqinaristi, Chairissa; Ainnurochimah, Hany Ica; Lukita Cahyani, Tiara Rizqy (Universitas Pahlawan Tuanku Tambusai, 2025)
The issue of plastic bottle waste has become an increasingly urgent environmental concern, particularly due to the low awareness among the general public, including elementary school students. The lack of education on waste management worsens this condition. This community service activity aims to provide education and creative training for students of SDN 2 Jari in processing plastic bottle waste into useful flower pots. The implementation methods include socialization, training, and hands-on practice, all designed using a participatory and educational approach. The results of the activity show high enthusiasm from students and teachers, improved student understanding of the importance of recycling, and positive changes in the school environment. The student-created flower pots serve not only as a symbol of creativity but also as an educational tool to strengthen environmental awareness values.